Insulating Composites Made from Sulfur, Canola Oil, and Wool. Issue 11 (10th March 2021) - Bu Najmah, Israa; Lundquist, Nicholas A.; Stanfield, Melissa K.; Stojcevski, Filip; Campbell, Jonathan A.; Esdaile, Louisa J.; Gibson, Christopher T.; Lewis, David A.; Henderson, Luke C.; Hasell, Tom; Chalker, Justin M.
Abstract: An insulating composite was made from the sustainable building blocks wool, sulfur, and canola oil. In the first stage of the synthesis, inverse vulcanization was used to make a polysulfide polymer from the canola oil triglyceride and sulfur. This polymerization benefits from complete atom economy. In the second stage, the powdered polymer was mixed with wool, coating the fibers through electrostatic attraction. The polymer and wool mixture were then compressed with mild heating to provoke S−S metathesis in the polymer, which locks the wool in the polymer matrix. The wool fibers imparted tensile strength, insulating properties, and reduced the flammability of the composite. All building blocks are sustainable or derived from waste and the composite is a promising lead on next‐generation insulation for energy conservation. Abstract : Three for one : Sulfur, canola oil, and wool are used to make a sustainable composite useful as energy‐saving insulation. The wool imparts improved mechanical properties and reduced flammability. All building blocks are sustainable or derived from waste.